Rock lobster: Lobby Loyde and the history of rock music in Australia - Beilharz, Peter (2012)
This article responds to the new and major work on Lobby Loyde by Paul Oldham. It focuses on the middle period of Loyde's career, from the Chicago-period Billy Thorpe and the Aztecs through to Lobby's work with Sharpie band (was it?) Coloured Balls, and connects and compares Lobby's trajectory to that of the post-Lobby Aztecs, as expressed in Sunbury, the 1972 parallel Australian event to Woodstock. Who led these processes, the bands or the crowds? If the crowd claimed a band, what happened to musical autonomy in this process? This was a moment when mass audience response became tribal, and opened the possibility that musicians were no longer in charge of their art. Trying to escape from the wiles of the music industry, these musicians instead seem to have become captive to their audiences. © The Author(s) 2012.